Thermoanaerosceptrum fracticalcis gen. nov. sp. nov., a Novel Fumarate-Fermenting Microorganism From a Deep Fractured Carbonate Aquifer of the US Great Basin - Hamilton-Brehm, Scott D.; Stewart, Laura E.; Zavarin, Mavrik; Caldwell, Matt; Lawson, Paul A.; Onstott, Tullis C.; Grzymski, Joseph; Neveux, Iva; Lollar, Barbara Sherwood; Russell, Charles E.; Moser, Duane P. (Frontiers in Microbiology, 2019)
With some exceptions, the deep fractured rock ecosystems across most of North America have not been studied extensively. However, the US Great Basin, in particular the Nevada National Security Site (NNSS, formerly the Nevada Test Site), has hosted a number of influential subsurface investigations over the years. This study focuses on resident microbiota within the fluids extracted from monitoring borehole U-3cn#5 at a depth of 691 meters below land surface, which intercepts a hydrogeological confined aquifer within Paleozoic fractured carbonate rocks. Analysis of the microorganisms living in this oligotrophic environment provides a perspective into microbial metabolic strategies required to endure prolonged hydrogeological isolation deep underground. Here we present a microbiological and physicochemical characterization of this environment and describe a novel bacterial genus isolated from the ecosystem. Strain DRI-13T is a strictly anaerobic, moderately thermophilic, fumarate-respiring member of the phylum Firmicutes. This bacterium grows optimally at 55°C and pH 8.0, can tolerate a concentration of 100 mM NaCl, and appears to obligately metabolize fumarate to acetate and succinate. Culture-independent 16S rRNA gene sequencing indicates a global subsurface distribution, while the closest cultured relatives of DRI-13T are Pelotomaculum thermopropionicum (90.0% similarity) and Desulfotomaculum gibsoniae (88.0% similarity). The predominant fatty acid profile is iso-C15:0, C15:0, C16:0 and C14:0. The percentage of the straight-chain fatty acid C15:0 is a defining characteristic not present in the other closely related species. The genome is estimated to be 3,649,665 bp, composed of 87.3% coding regions with an overall average of 45.1% G+C content. Strain DRI-13T represents a novel genus of subsurface bacterium isolated from a previously uncharacterized rock-hosted geothermal habitat. Our results describe a novel genus of bacterium combined with sequenced genome that provides insights into metabolism strategies of the deep subsurface biosphere. Based on our characterization analysis we propose the name Thermoanaerosceptrum fracticalcis (DRI-13T = DSM 100382T = ATCC TSD-12T).